PERFORMANCE OF MSCI ISLAMIC INDICES: A COMPARATIVE STUDY OF MALAYSIA AND GULF COUNTRIES - Jallow, Cherno (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: The Islamic finance industry has attracted increasing research interest, particularly in Islamic equity markets, in both academia and the corporate world during the past few decades. However, COVID-19 has caused a downturn in the Islamic stock markets. This study empirically explores and compares the performance of the MSCI Indices of Malaysia and each of the other MSCI Islamic indices in Gulf Cooperation Council (GCC) countries. Methods: To address the research questions, time series techniques, namely, the unit root test, cointegration, long-Run Structural Model (LRSM), Vector Error Correction Model (VECM), variance decomposition, impulse response, and persistence profile techniques, were used as the main method by utilizing monthly data from August 15, 2011, to November 15, 2020. Results: The results show that cointegration exists between the Malaysian Islamic indices and the six Islamic indices of GCC countries, which indicates that diversification benefits are limited in the long run because the indices move together. Additional results show a significant causality among the indices in both the short-run and long-run. (as shown in the LRSM and VECM tests). Conclusion and suggestion: The findings may have significant implications for portfolio diversification of Islamic indices among investors interested in Shariah-compliant securities in Malaysia and GCC countries, particularly in the COVID-19 era. Further research can be conducted for an in-depth analysis to examine the performance of these indices in terms of risk and return after the COVID-19 era using a more advanced technique.